Keragaman Genetik Kultivar Kelapa Dalam Mapanget (DMT) dan Dalam Tenga (DTA) Berdasarkan Penanda Random Amplified Polymorphic DNA (RAPD) - DONATA S. PANDIN (Pusat Penelitian dan Pengembangan Perkebunan, 2009)
Genetic Diversity of Mapanget Tall (DMT) and Tenga Tall (DTA) Coconuts based on Random Amplified Polymorphic DNA (RAPD)The objective of this research were to determine genetic diversity within and inter population of Mapanget Tall (DMT) and Tenga Tall (DTA) coconuts, and their genetic relationship based on RAPD ( ). Research was done at Plant Biology Laboratory of Center Research of Genetic Resources and Biotechnology, Institut Pertanian Bogor, from February to May 2007. The result showed that ten RAPD 10-primer used could separate DMT and DTA in each group. Genetic diversity within population was relatively narrow, so that selection in order to improve character in each population must be done selectively. Genetic relationship between DMT dan DTA populations was high (52%), so that crossing between these population will give highest heterosis effect.